2015
DOI: 10.3917/rdli.084.0059
|View full text |Cite
|
Sign up to set email alerts
|

Modes d’ajustement par le travail en temps de crise : des relations professionnelles sous tension

Abstract: International audienceCet article a pour objet de mettre au jour les processus d'ajustement des établisse-ments face à la crise, les caractériser et, conjointement, analyser la manière dont ils ont été discutés, négociés ou au contraire imposés par les directions. Sur le plan méthodologique, il s'appuie sur 15 monographies d'établissements réalisées dans le cadre des post-enquêtes à l'enquête Relations professionnelles et négociations d'entreprises (REPONSE) 2010-2011. Il montre que les établissements ne subis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
5
0
4
Order By: Relevance
“…We can interpret this finding either as an indication that industrial relations did not prevent adjustments, or that the actions of trade unions contained the scale of adjustments. We have no econometric umpire in this regard, but field studies over this period tended to work upon the hypothesis that trade unions were not in a position to block adjustments (Perez et al, 2015). The rise in the use of compromise agreements, which began well before the crisis, favours what we can consider to be joint management by trade unions and employers of the consequences of the crisis.…”
Section: Discussion Of Empirical Resultsmentioning
confidence: 99%
“…We can interpret this finding either as an indication that industrial relations did not prevent adjustments, or that the actions of trade unions contained the scale of adjustments. We have no econometric umpire in this regard, but field studies over this period tended to work upon the hypothesis that trade unions were not in a position to block adjustments (Perez et al, 2015). The rise in the use of compromise agreements, which began well before the crisis, favours what we can consider to be joint management by trade unions and employers of the consequences of the crisis.…”
Section: Discussion Of Empirical Resultsmentioning
confidence: 99%
“…Los datos obtenidos pueden interpretarse en dos sentidos diferentes, a saber: o bien las relaciones laborales no impidieron los ajustes o bien la actividad sindical sirvió para contener la magnitud de esos ajustes. No disponemos de un análisis econométrico que permita establecer cuál de estas dos lecturas es la correcta, pero los estudios de campo sobre este periodo avalan la hipótesis de la incapacidad de los sindicatos de poner freno a los ajustes (Perez et al, 2015). De hecho, el auge de las negociaciones de concesiones, iniciado mucho antes de la crisis, favorece lo que podría considerarse una gestión conjunta de las consecuencias de la crisis entre los sindicatos y los empleadores.…”
Section: Análisis De Los Resultados Empíricosunclassified
“…Aunque sus conclusiones se refieren a Irlanda, concuerdan con los análisis propuestos para el caso de Alemania (Bellmann y Gerner, 2012;Zagelmeyer, 2016) y podrían aplicarse a la situación de Francia o Gran Bretaña. Con una lectura algo más pesimista de los márgenes de acción sindical, Perez et al (2015) señalan que el deterioro de la coyuntura económica podría haber pesado en las negociaciones e incluso haber sido utilizado por los empleadores para imponer concesiones en casos en los que la crisis realmente no había tenido un impacto significativo. En el caso de Portugal, Távora y González (2016) llegan a identificar ciertas consecuencias de la crisis sobre el funcionamiento de la negociación colectiva a largo plazo.…”
Section: Análisis De Los Resultados Empíricosunclassified
“…These adjustments may of course have been made at different times, in line with a gradual deterioration in market conditions, as suggested by qualitative analyses (Perez et al, 2015;Roche & Teage, 2014). These monographic studies describe sequential processes in which the most easily implementable and the most socially consensual adjustments are made first (such as the non-renewal of temporary contracts, the abolishing of overtime, recourse to vacation leave, and wage moderation or freezes).…”
Section: Complementary Rather Than Substitutable Adjustmentsmentioning
confidence: 96%
“…Deroyon and Romans (2014) show that -all things being equal, and considering the trend in business volumes-establishments that belong to a group are more likely to be affected by workforce reductions. This also came out in the interviews conducted after the REPONSE survey, which revealed that some adjustments were made within the framework of relocation strategies implemented by groups in pursuit of profits (Perez et al, 2015). This effect is studied specifically by Cabannes et al (2013), who show that subsidiaries, especially among groups with an international presence, have made greater adjustments both to their business volumes and their workforce, and this cannot be explained entirely by a greater fall in demand.…”
Section: Economic and Financial Dependency Relationshipsmentioning
confidence: 96%